Clinico-mycological profile of onychomycosis in Assam, India - Borah, Nilakshi; Sharma, Ajanta; Hazarika, Debeeka (International Journal of Research in Medical Sciences, 2018)
Background: Onychomycosis (OM) is a common nail disorder caused by dermatophytes, non-dermatophyte moulds and yeasts. The increased prevalence of OM along with the wide range of associated fungi necessitates the accurate laboratory isolation and identification of the causative fungus for optimal management strategies. The aim of the study was to evaluate clinical, epidemiological and mycological characteristics of OM in a tertiary care hospital in Assam. Methods: It was a prospective hospital-based study. Hundred consecutive patients clinically diagnosed as OM were subjected to detailed history, clinical examination and investigations. Nail clipping and subungual debris of OM patients were subjected to KOH preparation and culture. Isolates were identified by colony characters, pigment production, microscopic morphology and biochemical tests. Results: The maximum number of OM cases belonged to the age group 21-30 years with a male preponderance (M:F=1.7:1). The commonest clinical type of OM was distal lateral subungual onychomycosis (DLSO) (51%). Toe nails OM was the most common presentation (54%). Trauma (35%) was the most common predisposing factor. Farmers (agro industry labourers) (23%) were found to be the most commonly affected group. Non-dermatophyte moulds (NDM) accounted for 38(47.5%) of OM cases followed by yeast 27(33.8%) and dermatophytes 15(18.8%). Conclusions: Early diagnosis and treatment is important to prevent distortion of the nails which can prevent loss of working efficiency of the commonly affected population of this region.